Chemical Study of the Fruits of Amomum celsum Lamxay & M.F. Newman of Vietnam - Giang, Phan Minh; Huong, Do Thi Viet; Binh, Nguyen Quoc (VNU Journal of Science: Natural Sciences and Technology; Vol 34 No 2DO - 10.25073/2588-1140/vnunst.4748, 2018)
The chemical study of the fruits of Amomum celsum Lamxay & M.F. Newman (family Zingiberaceae) applied extraction methods to extract polar compounds into a water-soluble fraction, preparative chromatographic techniques such as CC, Mini-C, preparative TLC on diferent adsorbents (Diaion HP-20, Sephadex LH-20, silica gel, and RP-18) to isolate compounds, and spectroscopic techniques such as ESI-MS and NMR to determine chemical structures. The study determined gallic acid, quercetin 3,7,3′,4′-tetramethyl ether, and 3,5-diacetoxy-1,7- bis (3,4-dihydroxy-phenyl)heptane. All of the compounds were isolated for the first time from A. celsum of Vietnam. Keywords Amomum celsum , Zingiberaceae, quercetin, diarylheptanoid References [1] Phạm Hoàng Hộ (1999), Cây cỏ Việt Nam, Nhà xuất bản Trẻ, Tp Hồ Chí Minh. [2] Lamxay V., Newman M. F., 69, 99-206 (2012). [3] Giang P. M., Son P. T., Matsunami K., Otsuka H. (2006), Chem. Pharm. Bull., 54, 139-140. [4] Giang P. M., Son P. T., Matsunami K., Otsuka H. (2012), Nat. Prod. Res., 26, 1195-1200. [5] Kamatham S., Kumar N., Gudipalli P. (2015), Toxicology Reports, 2, 520-529. [6] Yoshioka T., Inokuchi T., Fujioka S., Kimura Y. (2004), Z. Naturforsch., 59c, 509-514. [7] Kikuzaki H., Kobayashi M., Nakatani N. (1991), Phytochemistry, 30, 3647-3651.